GUIDELINES OF CHILD DEVELOPMENT CENTERS MANAGEMENT IN NEW NORMAL UNDER LOCAL ADMINISTRATIVE ORGANIZATION IN HUASAI DISTRICT NAKHON SI THAMMARAT PROVINCE - Katnim, Sirada; Yotharak, Maliwan; Onkong, Samit (Journal of MCU Nakhondhat, 2023)
The objectives of this research are 1) to study the conditions of child development center under the local administration organization. 2) to study the guidelines of child development centers management in New Normal under local administrative organization. and 3) to propose guidelines of child development centers management in the New Normal under local administrative organization. The research is conducted with integrated approaches of questionnaires with 89 respondents. The tools used are questionnaires, an interview, and a group conversation evaluation. The results of the study were as follows: 1) For the conditions of child development center under the local administrative organization, It is found that the conditions are of high level in general. The highest average is the administration of the child development centers, follow by the personnel, the academy and curricular activities, and the participation and operation support of the child development centers, the network promotion of pre-school child development at the level of local administrative organizations, district, province, and region. The facilities, environment and safety of the child development center has the lowest average. 2) In regard to the guidelines of child development centers management in New Normal under local administrative organization, technologies are applied to the administration of the child development centers, the personnel, the facilities, environment and safety of the child development centers, the academy and curricular activities, the participation and operation support of the child development centers, and the network promotion of pre-school child development at the level of local administrative organizations, district, province, and region. 3) For the result of the guidelines presentation, the scholars consider that the guidelines of child development centers management in New Normal under local administrative organization are appropriate, feasible, and useful.